The effectiveness of public health actions and services in Brazil: The indispensability of defining economic limits - Nielsen, Fernando Nardon; Contini, Alaerte Antonio Martelli (Seven Editora, 2023)
This research aimed to demonstrate the need to set a cost-effectiveness threshold for access to health. Health was discussed as a fundamental right, but not an absolute one due to the existence of limits that must be built considering the essentiality of the right and the scarcity of resources. The issues of the cost of the right to health and the scarcity of available resources was addressed to highlight the need for a cost-effectiveness threshold in Brazil. The themes were approached from the theoretical references of Stephen Holmes and Cass Sunstein to demonstrate that fundamental rights, including health, always demand positive actions from the State and, consequently, involve costs that can't be ignored. The research is conducted at the interface between human rights and legal economics. As a methodological process, documentary research related to data and bibliographic research is used. The study allowed the interpretation that there are historical, systemic and economic limits to access to health. Finally, there is a need to define a cost-effectiveness threshold in the SUS. DOI:https://doi.org/10.56238/colleinternhealthscienv1-137